PROBLEMATIKA PEMBELAJARAN BAHASA INDONESIA KETERAMPILAN MENYIMAK SEKOLAH DASAR (SD) - Handayani, Kisti; Retno Winarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Indonesian language learning in elementary schools plays an important role in developing students' language skills. One of the essential language skills is listening. However, in practice, listening learning in elementary schools still faces several issues. This article discusses several problems found in teaching Indonesian listening skills at the elementary level, such as students’ lack of interest, difficulties in understanding spoken texts, and the limited use of technology in the learning process. The article also identifies several solutions to address these issues, such as the use of more interactive teaching methods, integration of technology in lessons, and improved collaboration between teachers and students. The purpose of this article is to provide an overview of the problems in teaching Indonesian listening skills in elementary schools and offer potential solutions to overcome them.